Modelling of Electromagnetic Fields for Shielding Purposes Applied in Instrumentation Systems - Dagamseh, Ahmad M.; Al-Zoubi, Qasem M.; Qananwah, Qasem M.; Jaradat, Hamzeh M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In any sensory system, the Electromagnetic (EM) shielding of the channel-carrying signal is a fundamental technique to provide a noise-immune measurement system. Severe failures and uncertainty may occur if the external EM fields interfered with the measurements. Typically, the shielding is realized by enclosing the channel-carrying signal with thinconductive hollow structures. However, with such structures, it is required to provide access to the interior components from the outside, for wires’ connections, or better heat dissipation. This can be considered as a weakness in such the external magnetic fields can penetrate through the shielding structure. In this paper, the EM shielding effectiveness is considered for long hollow-cylinder structures with slots. The induced eddy current in thin-conductive shielding systems with slots together with the magnetic fields at different conditions are modeled. The objective is to determine the impact of the integrated slots along with the structure. The influence of the slots’ sizes (α) and position relative to the excitation magnetic field (i.e., the declination angle (β)) are investigated to evaluate the shielding effectiveness by means of the determination of the shielding factor. The results reveal the inherent relationship between the shield parameters and shielding effectiveness. The shielding effectiveness deteriorates by the slots’ integration within the shielding surface. However, decreasing the size of the slots improves the shielding, significantly, towards the shielding effectiveness of the continuous cylindrical structure. Additionally, utilizing the symmetry in the structure positioning the slots in the direction perpendicular to the magnetic field flux improves the shielding effectiveness, drastically. Such a model can be considered to evaluate the degree of effectiveness or success of integrating opening slots within the shielding structure, which can be applied to different types of instrumentation systems specifically at the sensor-electronics interface.